Patterns of motivation and learning during test-preparation of Korean adolescents: an experience sampling approach. Issue 2 (7th February 2022) - Lee, Minhye; Bong, Mimi
Abstract: Student motivation varies quickly, particularly under the pressing context. However, extant literature tends to focus on the individual, rather than contextual, differences in motivational patterns. We examined Korean adolescents' time-varying pursuits of achievement goals and learning outcomes using the experience sampling method, which collects individuals' subjective experiences repeatedly across time and context. A hyperlink to an 11-item online survey asking about achievement goals and learning outcomes at the moment was sent to 45 adolescents twelve times during the weekend before the midterm examination. The multilevel data revealed that mastery-approach goals predicted cognitive strategies better at the between-person level where they were treated as stable individual characteristics. In comparison, ability-approach and -avoidance goals retained their predictive power at the within-person level where their time-dependent changes significantly predicted several outcomes. The results demonstrate how adolescents' achievement goals fluctuated during a short time and how these changes predicted different learning outcomes.